Proceedings IEEE International Conference on Multimedia Computing and Systems
DOI: 10.1109/mmcs.1999.778590
|View full text |Cite
|
Sign up to set email alerts
|

JWeb: an HDM environment for fast development of web applications

Abstract: JWeb is a development environment for complex WWW applications, based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It has since evolved to encompass the full lifecycle (Guell et al 2000). JWeb starts at the definition of an HDM schema and provides an environment to assist in the whole process, including implementation (Bochicchio et al 1999). DPWA (Uden 2002) focuses on requirements (using Applied Cognitive Task Analysis (Militello and Hutton 1998)), usability requirements and Relational Navigation Analysis but does cover the whole lifecycle including maintenance.…”
Section: Those Methods Covering the Full Life Cyclementioning
confidence: 99%
See 3 more Smart Citations
“…It has since evolved to encompass the full lifecycle (Guell et al 2000). JWeb starts at the definition of an HDM schema and provides an environment to assist in the whole process, including implementation (Bochicchio et al 1999). DPWA (Uden 2002) focuses on requirements (using Applied Cognitive Task Analysis (Militello and Hutton 1998)), usability requirements and Relational Navigation Analysis but does cover the whole lifecycle including maintenance.…”
Section: Those Methods Covering the Full Life Cyclementioning
confidence: 99%
“…(Conallen 1999), WebComposition (Gellerson and Gaedke 1999), OOWS Modelling/notation WISD (Gnaho 2000), RSD (Janssen and Steen 2000), UWE (Koch 2000), FECWAD (Lu and Yeung 1998), HMT (Zoller 2001) Multimedia JWeb (Bochicchio et al 1999), MATILDA (Lowe et al 1996) Information systems/software engineering methods WISDM (Vigden 2002), AWE (McDonald and Welland 2001b), Turboprototyping (Ghosh 1999) Human-computer interaction Macweb (Nanard and Nanard 1995), UCDM (Fuccella 1997), URMDP (Alaa and Fitzgerald 2004), UCWD (McCracken and Wolfe 2004), DPWA (Uden 2002) Other CFEP (Norton 2000), WOOM (Coda et al 1998), RDF/WE (Kalpsing and Neumann 2000), RDF/XML framework (Christodoulou et al 2000), SWM (Griffiths et al 2002), WebML? (Tongrungrojana and Lowe 2003), AWARE (Bolchini and Paolini 2004), QEM (Olsina et al 2000), HFPM (Olsina 1997) Software Qual J (2009) 17:125-150 137 understanding of research outcomes by practitioners, or as suggested above, that research outcomes are not yet suited to practical development (Lowe 2003) and the field has not yet matured enough to have a viable approach to applied research.…”
Section: Object Oriented Analysis and Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides AutoWeb and WebML, which have been discussed above, these include OOHDM-Web [Schwabe et al 1999], JWeb [Bochicchio et al 1999], and OO-H [Gómez et al 2001]. OOHDM-Web, which represents an evolution of OOHDM in the Web context, is an environment for implementing Web applications designed by the OOHDM method.…”
Section: Related Workmentioning
confidence: 99%